Developing a digital learning model integrating PCK-SJT to enhance pre-service arts teachers' professional competence - Prasetyo, Abdul Rahman; Aulia, Fikri; Kusumaningrum, Shirly Rizki (Asatiza: Jurnal Pendidikan, 2025)
This study addresses the critical need for effective digital learning tools in teacher education by developing and evaluating a novel learning model that integrates Pedagogical Content Knowledge (PCK) with Situational Judgement Tests (SJT) within a Learning Management System (LMS) for pre-service Arts and Culture teachers in Indonesia. Grounded in the Technological Pedagogical Content Knowledge (TPACK) framework, the research employed a Research and Development approach using the ADDIE model, culminating in a limited trial with 20 participants. The findings demonstrate the model's efficacy in significantly enhancing professional competencies, with 80% of participants exhibiting improved reflective pedagogical reasoning and 90% affirming the high authenticity of the SJT scenarios. The study contributes an innovative, empirically validated framework for competency-based teacher education that effectively bridges the theory-practice gap, while also highlighting the need for future large-scale implementations to address limitations related to sample size and contextual focus.